George W. Bush's healthy forests: reframing the environmental debate - Vaughn, Jacqueline, author; Cortner, J. Hanna, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2005)
The authors detail Bush administration reframing of America's environmental debate, identifying players, events, and strategies that expedited a policy shift that impacts public lands and long-standing avenues of public involvement.
Introduction: a reversal of fortunes: reframing the environmental debate -- 1. From silents springs to luntzspeak: environmental policy and George W. Bush -- 2. The right to object: historic landmarks in the development and use of appeals -- 3. Appellants, strategies tactics, and outcomes -- 4. The wildland-urban interface and the fire-appeals interface -- 5. Reform by legislation: the healthy forests restoration act -- 6. Reform by rulemaking -- Conclusion: the spillover effect.
Keywords: Forest policy -- United States; Forest management -- United States; Forest management -- Environmental aspects -- United States